NetSecBed: A Container-Native Testbed for Reproducible Cybersecurity Experimentation - Bitzki, Leonardo; Kreutz, Diego; Heinrich, Tiago; Bertholdo, Leandro; Quincozes, Silvio; Fideles, Douglas; Nogueira, Angelo (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2026: Anais do XVIII Simpósio Brasileiro de Computação Ubíqua e PervasivaDO - 10.5753/sbcup.2026.23835, 2026)
Cybersecurity research depends on reproducible evidence, traffic traces, logs, and labeled datasets, but public datasets are often static and difficult to re-execute, especially in heterogeneous multi-protocol environments. This paper presents NetSecBed, a container-native, scenario-oriented testbed for controlled generation of network evidence and execution artifacts in IoT, IIoT, and pervasive settings. NetSecBed integrates 60 attack scenarios, 9 target services, and benign traffic generators as single-purpose containers, with plug-and-play extensibility and traceability through declarative specifications. Its pipeline automates parameterized execution, packet capture, log collection, service probing, feature extraction, and dataset consolidation. The result is a repeatable, auditable, and extensible framework that reduces operational bias and supports continuous dataset renewal.